Meningkatkan Keterampilan Membuat Kacang Kulit Asin Melalui Metode Explicit Instruction Bagi Anak Tunagrahita Ringan Kelas X di SLB Al-Azhar Bukittinggi - Dyah Laras Sarira; Zulmiyetri Zulmiyetri (Universitas Negeri Padang, 2021)
In this study, discussing the problems found in SLB Al-Azhar Bukittinggi, the researchers found that there were two class X mild mentally retarded students who had the ability to make salted shell nuts. However, during the lesson, the teacher only used the lecture method when making salted peanut shells. Efforts that can be done for this is to teach to make salted peanut shells using an explicit instruction method. The aim of this study was to see the improvement process in making salted shell nuts. The type of research used is classroom action research. Making salted peanut shells using an explicit instruction method provides more opportunities for children to more easily remind each of the manufacturing processes. By doing it step by step, making it easier to understand. The explicit instruction method can improve the skills of making salted skin peanuts for mild mentally retarded children in class X at SLB Al-Azhar Bukittinggi